Students' Perspectives On The Utilization Of 'Splash' As A Tool In Learning Listening Skills. - Novita Kusumaning Tyas; Athiyah Salwa (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Currently, mobile technology developments are increasing rapidly. Crompton and Burke (2018) conveyed that smartphone as one of mobile technology is is rapidly advancing. Approximately 90% of students possessed a smartphone, and a few even had multiple mobile phones. (Wong et al., 2010; Bhati & Song, 2019). This study aimed to examine how the students perceive the utilization of “Splash” as a media on learning listening skill. Splash is one of android program that developed by the English team in Stekom University. It is made for improve students’ listening skill and grammar skill. This research used quantitative descriptive. The sample consists of 50 students who taken language class. The result showed that there are positive attitudes from the students about the usage of “Splash” to improve listening skill. They can use it every time and everywhere without worried running out of internet package because this application doesn’t need internet package to use. The students also found that the content of this application is interesting. They also got post-activity activities and tasks to help them improve their skills.